Resource Orchestration and Scaling‐up of Platform‐Based Entrepreneurial Firms: The Logic of Dialectic Tuning - Zeng, Jing; Yang, Yunlu; Lee, Soo Hee (Journal of Management Studies, 2023)
AbstractThe emergence of platform‐based entrepreneurial firms (PBEFs) and their rapid scaling holds considerable implications for the theory and practice of firm growth in the digital economy. Building on the resource‐based view, we seek deeper insights into the question of how PBEFs orchestrate resources to scale up in the context of platform ecosystems. We conduct an in‐depth longitudinal case study of Tencent, one of the largest PBEFs in the world, and develop an inductive process model based on the logic of ‘dialectic tuning’. We uncover the specific actions and capabilities that PBEFs possess and employ to scale up a platform ecosystem, as manifested in a complementary set of concrete organizational practices enacted at different stages of the growth trajectory. We unveil an important boundary condition that has hitherto remained implicit in the literature on firm growth driven by platform‐based business models. Our findings diverge from the conventional perspective which predominantly associates firm growth with the characteristics of internal resources and capabilities. We argue that the relational properties of interaction and integration between internal and external resources are what gives rise to the capabilities needed to scale up a platform. Thus, we extend and refine the resource‐based view by explaining the evolving patterns of resource orchestration and management of PBEFs in terms of the interplay between the focal platform and its ecosystem partners.